Business research methods - Dangi, H. K.; Dewen, Shruti (Andover Cengage Learning, 2016)
Business research methods presents terms and techniques of research in a simple and crisp manner. The aim of the book is to present research methods covering all aspects of undergraduate and postgraduate curricula of commerce and management. The book will also be of substantial benefit to doctoral students. ; The book covers topics related to complete research process from problem identification to report writing. The book also provides a wide range of real-life examples and illustrations.
Bibliography: P 372-374; Index: P 375-379
English
Keywords: Crisp manner; Business research methods